Lactate exposure shapes the metabolic and transcriptomic profile of CD8+ T cells - Barbieri, Laura; Veliça, Pedro; Gameiro, Paulo A.; Cunha, Pedro P.; Foskolou, Iosifina P.; Rullman, Eric; Bargiela, David; Johnson, Randall S.; Rundqvist, Helene (Frontiers in Immunology, 2023)
CD8+ T cells infiltrate virtually every tissue to find and destroy infected or mutated cells. They often traverse varying oxygen levels and nutrient-deprived microenvironments. High glycolytic activity in local tissues can result in significant exposure of cytotoxic T cells to the lactate metabolite. Lactate has been known to act as an immunosuppressor, at least in part due to its association with tissue acidosis. We show here that the lactate anion is well tolerated by CD8+ T cells in pH neutral conditions. We describe how lactate is taken up by activated CD8+ T cells and is capable of displacing glucose as a carbon source. Activation in the presence of a pH neutral form of lactate significantly alters the CD8+ T cell transcriptome, including the expression of key effector differentiation markers such as granzyme B and interferon-gamma. Our studies reveal the novel metabolic features of lactate utilization by activated CD8+ T cells, and highlight the importance of lactate in shaping the differentiation and activity of cytotoxic T cells.